Sosialisasi Pendidikan Anti Korupsi Sikap Disiplin pada Anak yang Ketergantungan Gadget Melalui Permainan Lego - Eka Selvi Handayani; Agustinus Bernadinus Pati; Maria Clarita; Uswatun Khasanah; Ester Tabita; Widya Nanda; Irene Avrilia Nirmala (BADAN PENERBIT STIEPARI PRESS, 2026)
corruption is a serious issue that must be addressed from an early age through character education. Children who are overly dependent on gadgets tend to experience a decline in discipline and moral values. Therefore, a socialization program on anti-corruption education using a creative method through LEGO play was organized, entitled